Kinetics and mass transfer of esterification of acrylic acid with 2-ethyl hexanol in a tubular packed bed reactor - Chin, Sim Yee; Abdulbari, Hayder A.; Cheng, Chin Kui (2017)
The global demand of 2-ethylhexyl acrylate (2EHA) market has witnessed a significant growth in the past few years and this growth is anticipated to increase in the coming years. 2EHA is one of the basic organic building blocks that mainly used in the production of coatings, adhesives, super-absorbents, thickeners and plastic additives. As the demand increases, the productions of 2EHA need to be innovated so that it can be produced in a cheaper price. The use of homogeneous catalyst in the commercial process shows that these catalysts are hard to separate from the reaction medium, hence unable the reuse of the catalysts and complicate the separation process. It also promotes side reaction which resulting in expensive downstream processes. The employment of heterogeneously catalysed process in a tubular reactor is anticipated to a cheaper process since it can enable the reuse of catalyst, minimise the hazardous waste generation due to the homogeneous catalyst, and eliminate the occurrence of side reaction and hence increasing the yield of desired product. In the present study, the best catalyst was identified and the residence time distribution of the tubular packed bed reactor was examined prior the study on the effect of important operating parameters on the esterification of Acrylic Acid (AA) with 2-Ethyl Hexanol (2EH) for the production of 2EHA in a tubular packed bed reactor. The reaction kinetics were also evaluated. Employing the best catalyst, DIAION PK-208 in a tubular packed bed reactor for the esterification of AA and 2EH, the highest yield and conversion, 3.29% and 44.3 % respectively were obtained at the reaction temperature of 95°C, initial feed molar ratio of AA:2EH of 1:3 and catalyst loading of 5 g. The discrepancy of the yield and conversion was ascribing to the AA adsorbed on the resin. The tubular packed bed reactor was non-ideal in mixing. The kinetic studies show that the Eley-Rideal (ER) was the best kinetic model to correlate the rate of consumption AA and production of 2EHA. The data obtained can be used as a baseline information to develop a bigger scale of packed bed reactor for the production of 2EHA.